(untitled) (Research, Society and Development, 2022)
Among the research methods, the Case Study is one of the most used in qualitative research today. However, research using this method is still viewed with some suspicion by the academic world, receiving criticism due to its lack of rigor and for being in a still evolving phase, thus suffering a shortage of well-defined strategies and techniques. Thus, the objective of this article is to present characteristics of the Case Study, point out advantages and applications in EPT, based on productions of several authors, thus constituting a bibliographic type study. The option to approach the case study modality was based on its wide use in the social sciences, as well as its scope, consisting of a complete process: planning, specific approaches and data analysis. Not just a data collection or research planning tactic. As it is an empirical investigation within a real-life context, it is concluded that the Case Study, if applied correctly, can significantly contribute to research in Vocational and Technological Education.